Mobility in times of Covid-19: Effects of immobility on air transport - Santos, Rosemárcia Ribeiro dos; Edra , Fatima Priscilla Morela (Seven Editora, 2023)
The year 2020 brought with it several changes in society as a result of the emergence of the pandemic caused by the new Corona Virus (SARS CoV-2), initially an epidemic located in the province of Wuhan in China, but which quickly spread to the whole world, becoming a pandemic that has caused thousands of deaths, impacts on human life and economy of most countries around the globe. Like many sectors of the world economy, the airline industry is facing a severe economic crisis in the pandemic scenario due to travel restrictions (physical immobility) and border closures around the world. Based on the current situation experienced by air transport, this study aims to verify how the restrictions of physical displacement of individuals in the current pandemic scenario have impacted the Brazilian air industry through bibliographic research. As a result, Brazilian air transport has lost a significant number of passengers and that, although it is in a moment of crisis, it will need to devise strategies to survive the pandemic chaos and invest in adapting to the post-pandemic scenario. DOI:https://doi.org/10.56238/emerrelcovid19-023